XML Processing in Java - Laitinen, Tapio (2005)
Jyväskylä: University of Jyväskylä, 2005. 40 pages. Bachelor's Thesis. XML and Java have both gained considerable attention in last few years. In this thesis, different mechanisms for processing XML in general, and in Java in particular, are examined. These mechanisms are the three XML processing models, SAX, DOM and JDOM, and XSL Transformations (XSLT). The purpose of this thesis is to examine how XML processing or, more accurately, parsing, interpreting, and transforming is done in Java programming language. In addition to that, some evaluation of suitability of Java for this task is carried out. Complete code examples of different XML processing techniques are provided in appendices, but they are kept relatively short because extensive example applications are not appropriate for this thesis. Every processing model has its strengths and weaknesses which makes some of the models more suitable for a particular task than the others. This thesis helps in making a choice between the processing models by listing some of their benefits and drawbacks. All in all, Java seems to suit adequately for most XML processing applications.